Diagnosis and Treatment of Connective Tissue Disease-Associated Interstitial Lung Disease - Vij, Rekha (American College of Chest Physicians, 2013)
Interstitial lung disease (ILD) is one of the most serious pulmonary complications associated with connective tissue diseases (CTDs), resulting in significant morbidity and mortality. Although the various CTDs associated with ILD often are considered together because of their shared autoimmune nature, there are substantial differences in the clinical presentations and management of ILD in each specific CTD. This heterogeneity and the cross-disciplinary nature of care have complicated the conduct of prospective multicenter treatment trials and hindered our understanding of the development of ILD in patients with CTD. In this update, we present new information regarding the diagnosis and treatment of patients with ILD secondary to systemic sclerosis, rheumatoid arthritis, dermatomyositis and polymyositis, and Sjögren syndrome. We review information on risk factors for the development of ILD in the setting of CTD. Diagnostic criteria for CTD are presented as well as elements of the clinical evaluation that increase suspicion for CTD-ILD. We review the use of medications in the treatment of CTD-ILD. Although a large, randomized study has examined the impact of immunosuppressive therapy for ILD secondary to systemic sclerosis, additional studies are needed to determine optimal treatment strategies for each distinct form of CTD-ILD. Finally, we review new information regarding the subgroup of patients with ILD who meet some, but not all, diagnostic criteria for a CTD. A careful and systematic approach to diagnosis in patients with ILD may reveal an unrecognized CTD or evidence of autoimmunity in those previously believed to have idiopathic ILD.